Preparation of gelatinous gold nanoparticles by pulsed laser ablation - Darroudi, Majid
Colloidal gold nanoparticles (Au-NPs) were successfully prepared using a nanosecond-pulsed Nd:YAG laser, lambda = 1,064 nm, with laser fluence of approximately about 360 mJ/pulse, in an aqueous gelatin solution. In this work, gelatin was used as a stabilizer, and the size and optical absorption properties of samples were studied as a function of the laser ablation times. The results from the UV-Vis spectroscopy demonstrated that the mean diameter of Au-NPs decrease as the laser ablation time increases. The Au-NPs have mean diameters ranging from approximately 19 to 7 nm. Compared with other preparation methods, this work is clean, rapid, and simple to use.